Supply Chain Management Sustainability Index (SCMSI): a comparative study between Malaysian and Thailand companies / Roshima Said ... [et al.] - Said, Roshima; Joseph, Corina; Rahmat, Mariam; Abdullah, Wan Nailah; Radjeman, Leily Adja; Chattrarat, Phuttiwat (2019)
Malaysia, as a developing country has continued to emphasize the importance of environmental, social and governance (ESG) matters among Malaysian public-listed companies. Datuk Seri Abdullah Ahmad Badawi, Malaysia's fifth Prime Minister in his 2007's budget speech mentioned that the Malaysian public-listed companies are required to furnish their corporate social responsibility (CSR) initiatives in the annual reports. Companies must report on the reasons regarding the failure to provide ESG information in the annual reports. Not only that, Malaysian government has shown its supports on the 2030 Development Agenda and its SDG, whereby the main purpose of these 17 SDG are to sustain the preservation of planet and prosperity of society by emphasizing the importance of good health and well-being, gender equality, quality education, as well as responsible consumption and production. Therefore, it is necessary for corporations of a country to have a reliable, relevant and standardized sustainability supply chain management (SSCM) reporting practice. It is essential for a company to disclose its supply chain management information in a proper way that will enable the stakeholders to evaluate the firm's supply chain management performance efficiently. Therefore, the development of supply chain management sustainability index (SCMsi) is timely. The SSCM disclosure strategy is also important for companies in providing information to stakeholders. Marshall et. al. (2016) highlighted that many companies have limited visibility of their supply chain information, have a poor understanding of their capabilities for capturing and reporting this information, and have not overtly considered their supply chain information disclosure strategy. This would impede companies to disclose a comprehensive information to stakeholders. It is advanced that a comprehensive SSCM disclosure checklist is imperative for Malaysian public companies as most standards and guidelines on SSCM are from western countries. It is hoped that the new SSCM specifically developed for Malaysia can become a benchmark for reporting a more relevant and accurate SSCM by companies.